Implementasi Penggunaan Sistem Aplikasi Guru Surabaya (Siagus) Dalam Pencairan Tunjangan Kinerja (Tukin) Guru Di Dinas Pendidikan Kota Surabaya - Mansyuri, Arif; Jamalia, Jamalia; Assis Faizul Anany; Isma Indra Wahidatun Nisa (Proceedings of Annual Conference on Islamic Educational Management, 2021)
In the current era of science and technology is growing very rapidly, the Surabaya City Education Office has now created new innovations to facilitate the performance of educators. Surabaya Teacher Application System is an internet-based support facility and a network of data management procedures developed in an educational institution organization in Surabaya City. This article aims to describe the influence of the use of the Surabaya Teacher Application System (SIAGUS) on teacher performance allowance (TUKIN) in the Surabaya City Education Office that supports teacher performance. The type of research used is descriptive qualitative research with the direct object of teachers in the Surabaya education office. The main findings in this study are the implementation of the Surabaya Teacher Application System (SIAGUS) application in the disbursement of performance allowances (TUKIN) in terms of ease of administrative services, the fulfillment of teacher rights in Surabaya, and the increasing motivation of teachers in Surabayai